ANALISIS ZAT PEWARNA PADA KEPAH (Polymesoda erosa) ASIN YANG DIJUAL DI PASAR SENTRAL DAN PASAR SUKARAMAI DI KOTA MEDAN TAHUN 2013 - vina andriani; indra chahaya; wirsal hasan (Lingkungan dan Kesehatan Kerja, 2014)
Salty mussel is not one of fast food that need further processing in order can be consumed. Salty mussel is always sold with the bright yellow and orange color in order to look fresh and interesting. But sometimes dyes used are dyes that are not safe to eat, so it so necessary to identify the type and level of dyes used whether qualified or not. This research is a descriptive research. Samples were taken in total sampling from the Central and Sukaramai market on Medan city, which amounts to 10 samples. And than, samples were examined in the Medan Health Laboratory. Examination conducted on the samples before and after washing. Dye analysis conducted by qualitative and quantitative test. The results showed that of the 10 samples were not washed, there were 9 samples that do not qualify for consumption because it contains a banned dye (Orange RN) and contain dyes that are allowed (sunset yellow and tetrazine) in the amount of 52-560 mg/kg who have exceeded the allowed limit 30 mg/kg. And the results of a study of a sample after washing showed that there is a decrease of dye concentration of 0.3 - 1.8 mg/kg. However, the results of the study remains that of the 10 samples after washing there are 9 samples that do not qualify for consumption and only 1 sample safely consumed by Permenkes RI No.722/Menkes/Per/IX/1988. Therefore, it is important to have monitoring, evaluation and counseling on the use of food additives in particular dyes that use is in accordance with the applicable regulations.